COMPARING THE FINANCIAL PERFORMANCE OF REGIONAL DEVELOPMENT BANKS (RDB) LISTED ON IDX PRE AND POST THE ANNOUNCE COVID-19 IN INDONESIA - Ana Dwi Pertiwi (International Journal Management and Economic, 2023)
The economy of Indonesia has suffered as a result of Covid-19. However, although a pandemic negatively impacts the current economic conditions, the overall resilience of Regional Development Banks has not been affected. RDBs are organizations of financial institutions that work to improve the economic conditions of an area by assisting with finance for regional development. Comparing the financial performance of RDB listed on the IDX, both pre and post the announcement of covid-19, using the CAMEL approach and calculating ratios based on CAR, NPL, ROA, ROE, NIM, BOPO, and LDR was the purpose of this study. In addition, this research used a comparison methodology, which compared the economic performance of RDB listed on the IDX pre and post-announcement of the covid. According to the findings of this research, there was no significant difference in the CAR, NPL, or ROE of RBD pre and post-announcement of the Covid-19. The findings of this study demonstrate, however, that there are significant differences in ROA, NIM, and BOPO of RDB both pre and post-announcement of the covid-19.